As três esferas do socialismo democrático / The Three Spheres of Democratic Socialism - Thompson, Michael J. (Revista Direito e Práxis, 2022)
DOI: 10.1590/2179-8966/2022/66939. Abstract This essay charts a normative framework to defend the politics and principles of democratic socialism. It argues that the tradition of democratic socialism can be best understood as consisting of the connection of three spheres of social reality: the material, the political and the cultural. Each also possesses a respective principle that organizes them, that of cooperative interdependence, non-subordination, and self-realization. The paper ends by considering how social movements can see their own struggles in terms of the structure of these three spheres. Tradução Cauê Marques, Universidade do Estado do Rio de Janeiro, Rio de Janeiro, Rio de Janeiro, Brasil. E-mail: cauemarques_@hotmail.com. Revisão Lucas Dias, Universidade do Estado do Rio de Janeiro, Rio de Janeiro, Rio de Janeiro, Brasil. E-mail: olucasdias@gmail.com.